The Influence of Principal Supervision, Principal's Pedagogic Competence, and Principal's Welfare on the Performance of State Junior High School Teachers in North Penajam Paser Regency - Sugiarti, Isa; Wulandari, Ayu; Rifqi, Ainur; Khamidi, Amrozi (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to examine the influence of principal supervision, principals’ pedagogical competence, and principals’ welfare on teacher performance in public junior high schools in Penajam Paser Utara Regency. A quantitative approach with an ex post facto causal design was applied. The population consisted of 447 teachers, and a sample of 212 teachers was selected using the Slovin formula with a 5% margin of error. Data were collected through structured questionnaires using a four-point Likert scale. Instrument validity was tested using Pearson Product Moment correlation, while reliability was measured using Cronbach’s Alpha. Data analysis employed multiple linear regression with SPSS version 22, following classical assumption tests including normality, multicollinearity, and heteroscedasticity. The findings indicate that principal supervision, principals’ pedagogical competence, and principals’ welfare each have a significant effect on teacher performance. Partially, principal supervision improves teachers’ professional performance through systematic and continuous academic guidance. Principals’ pedagogical competence also has a positive impact by strengthening instructional leadership and enhancing effective teaching practices. Additionally, principals’ welfare contributes positively by fostering a stable and supportive organizational climate. Simultaneously, the three independent variables significantly affect teacher performance (F = 220.970, p 0.05), demonstrating that the combination of supervision, competence, and welfare plays a crucial role in improving teacher performance. These results suggest that enhancing teacher performance requires an integrated approach that combines effective supervision, strong pedagogical leadership, and adequate welfare conditions. Strengthening these factors is essential to support sustainable improvements in the quality of education in public junior high schools.